2005
DOI: 10.1073/pnas.0408436102
|View full text |Cite
|
Sign up to set email alerts
|

Association of tissue-specific differentially methylated regions (TDMs) with differential gene expression

Abstract: Early studies proposed that DNA methylation could have a role in regulating gene expression during development [Riggs, A.D. (1975) Cytogenet. Cell Genet. 14, 9 -25]. However, some studies of DNA methylation in known tissue-specific genes during development do not support a major role for DNA methylation. In the results presented here, tissue-specific differentially methylated regions (TDMs) were first identified, and then expression of genes associated with these regions correlated with methylation status. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
227
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 316 publications
(242 citation statements)
references
References 31 publications
11
227
0
2
Order By: Relevance
“…Restriction landmark genomic scanning, a classic technique for global analysis of tissue-specific differentially methylated genomic regions (39,40), requires large amounts of sample DNA despite its limited sensitivity for detecting expected rare events, making microdissection of embryonic tissues neither suitable nor practical. We therefore decided to use an in vitro chondrogenesis assay of isolated MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Restriction landmark genomic scanning, a classic technique for global analysis of tissue-specific differentially methylated genomic regions (39,40), requires large amounts of sample DNA despite its limited sensitivity for detecting expected rare events, making microdissection of embryonic tissues neither suitable nor practical. We therefore decided to use an in vitro chondrogenesis assay of isolated MSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Recent results, mostly obtained by genome wide approaches to study DNA methylation, do confirm a role for DNA methylation in tissue specific gene expression. One of these genome wide approaches known as Restriction Landmark Genome Scanning (RLGS) has enabled to identify in six mice tissues a large number of differentially methylated regions (TDMs) which exhibit a tissue-specific expression pattern that is consistent with methylation status and a role in tissue differentiation [50]. Furthermore, Ching et al [51], by using BAC microarray have identified CpG island loci that are methylated in a tissue-specific manner in normal human tissues, including SHANK3 whose differential methylation in different tissues was also evolutionary conserved.…”
Section: Cpg Dinucleotides Location and Func-tionmentioning
confidence: 99%
“…DNA is methylated at a cysteine base pair, most often at a CpG dinucleotide (CpG site) 9. Methylation of CpG sites in the promoter region of a gene is commonly associated with repression of gene expression 10, 11, 12. DNA methylation occurs through the activity of DNA methyltransferases (DNMTs), particularly DNMT1 postdevelopment 13, 14, 15.…”
Section: Introductionmentioning
confidence: 99%